Rare earth silicate environmental barrier coatings: Present status and prospective. Issue 8 (1st June 2017) - Xu, Yue; Hu, Xunxun; Xu, Fangfang; Li, Kunwei
Abstract: Due to drastic decreasing in mechanical properties at relative high temperature, traditional nickel based super alloys are replaced by Si-based non-oxide ceramics in the application of high temperature aero-engines. In order to reduce the spallation and deformation of aero-engine blades in the environment containing high temperature water vapor and oxygen, protection coatings on the surface of the ceramics are required. Owing to high temperature stability, superior oxidation resistance and corrosion resistance properties, rare earth (RE) silicates are promising as candidates and play an important role in improving the high-temperature mechanical/thermal properties of Si-based non-oxide ceramics. In this review, recent progress in the research and development of environmental barrier coatings (EBCs) are summarized. Development of EBCs is presented, and the multi-scale structures and properties of each part are introduced. In addition, the merits and demerits of each preparation technique are discussed. As a promising candidate for the application in high temperature aero-engines, Si/mullite/Lu2 Si2 O7 –Lu2 SiO5 EBCs are highlighted.